2019
DOI: 10.1590/2317-1545v41n3213139
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effects of TiO2 nanoparticles and sodium nitroprusside on seed germination and seedling growth of wheat under PEG-stimulated drought stress

Abstract: Seed germination and early seedling growth are sensitive to drought stress in wheat. A factorial experiment was arranged based on a completely randomized design with three replicates to study the impacts of TiO2 nanoparticles (TiO2 NPs: 0, 500, 1000 and 2000 mg.L) and sodium nitroprusside (SNP: 0 and 100 μM), as NO donor, on seed germination and seedling growth of wheat under polyethylene glycol (PEG)-induced drought stress (0, -0.4 and -0.8 MPa). Our results revealed that PEG-stimulated drought stress signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…10 Many studies have shown that nanomaterials may also enhance the tolerance of plants to external stresses such as drought, flooding, cold, heat, salinity and heavy metal stress. 11 For example, TiO 2 NPs have been reported to improve plant growth under drought 12 or cold 13 stress. CuO NPs as low as 1 mg L −1 can enhance the tolerance to pathogens of tomato grown in soil infested with Fusarium oxysporum.…”
Section: Introductionmentioning
confidence: 99%
“…10 Many studies have shown that nanomaterials may also enhance the tolerance of plants to external stresses such as drought, flooding, cold, heat, salinity and heavy metal stress. 11 For example, TiO 2 NPs have been reported to improve plant growth under drought 12 or cold 13 stress. CuO NPs as low as 1 mg L −1 can enhance the tolerance to pathogens of tomato grown in soil infested with Fusarium oxysporum.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the SNP may have Journal of Seed Science, v.42, e202042041, 2020 induced breakdown of the superoxide ion, eliminating the reactive oxygen species produced and reducing oxidation. Yet, it is possible that the oxygen produced in this process may also have been consumed in respiration, affecting seed metabolic activity and, consequently, increasing germination percentage (Faraji and Sepehri, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in root size when the seeds are primed with SNP can be explained through the idea that it performs a role similar to plant hormones, such as cytokinins, gibberellin, and auxin, due to an ability of inducing cell division and proliferation of the plant, as well as tissue differentiation. Salt stress may also have brought about relaxation of the cell wall and induction of cell extension, which consequently has a greater contact surface for absorption of water and greater ability to take up oxygen released by the product during priming (Faraji and Sepehri, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations